IMPROVING FOURTH-GRADE STUDENTS' SCIENCE AND SOCIAL STUDIES LEARNING OUTCOMES THROUGH THE EXAMPLE NON-EXAMPLE LEARNING MODEL ASSISTED BY POWERPOINT MEDIA AT SD NEGERI 104/II SUNGAI PINANG: PENINGKATAN DAN HASIL BELAJAR IPAS SISWA MELALUI MODEL EXAMPLE NON EXAMPLE BERBANTU MEDIA POWERPOINT PADA KELAS IV SEKOLAH DASAR NEGERI 104/II SUNGAI PINANG - Serly Devica; Apdoludin; Megawati (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Abstract This study aims to improve the learning process and learning outcomes of IPAS for fourth-grade students at SD Negeri 104/II Sungai Pinang through the implementation of the Example Non-Example model assisted by PowerPoint media. The method used was Classroom Action Research (CAR), conducted in two cycles consisting of the stages of planning, implementation, observation, and reflection, with 30 students as the research subjects. Data collection techniques were carried out through observation, tests, and documentation, while data analysis used qualitative and quantitative approaches. The results showed that there was an improvement in students’ learning outcomes at each stage. In the pre-action stage, 9 students (30%) achieved mastery, increasing in Cycle I to 14 students (46.67%), and in Cycle II increasing to 26 students (86.67%). In addition, the learning process also improved, marked by increased student activeness in discussions, confidence in expressing opinions, and the ability to conclude the material. Thus, it can be concluded that the implementation of the Example Non-Example model assisted by PowerPoint media is effective in improving the learning process and learning outcomes of IPAS students. Keywords: Learning Outcomes, Learning Process, Example Non-Example, PowerPoint, IPAS